Tribological Behaviour of Graphene Coated Bearing Steel (EN31) - Moharana, R; Sengar, S S; Badhan, B; Rao, U S; Gautam, R K; Tyagi, R (Institute of Physics Publishing, 2019)
The present investigation is on the tribological behaviour of graphene coated bearing steel (EN31). Though bearing steel has excellent mechanical properties but its wear properties are inadequate. To enhance its wear properties, bearing steel was coated by graphene. Graphene is a very unique and peculiar material. It has excellent mechanical, chemical, electrical, magnetic and optical properties. Furthermore, it is light in weight which makes it one of the most sought after materials in the research world. To improve the adhesion property between graphene and bearing steel, bearing steel was first coated with nickel using electroplating technique. Then graphene was coated by CVD technique. To analyse the characteristics of graphene, Raman spectroscopy was carried out. The friction and wear tests were performed at constant load of 1 N and different speeds of 0.05 m/s, 0.075 m/s and 0.1 m/s for the tribological analysis of the materials. After wear, the worn out surfaces were further investigated by using scanning electron microscope (SEM). From the present investigation it has been observed that coated bearing steel shows improved tribological characteristics.
Keywords: Bearing steel; Friction; Graphene; Tribology; Wear